UTILIZATION STATUS OF RAINBOW PRAWN (Parapenaeopsis stylifera) RESOURCE IN MUKOMUKO WATERS, BENGKULU - Erisal, Arief; Wiyono, Eko Sri; Zulkarnain, Zulkarnain; Taurusman, Azbas (Jurnal Penelitian Perikanan Indonesia, 2024)
Shrimp resources in Mukomuko waters have been exploited by minitrawl since the 1980s.  High fishing pressure has been reported due to intensive trawling in a relatively small fishing area. Appropriate management measures are needed to maintain the sustainability of the shrimp resource. The aim of this study was to assess the exploitation status of the shrimp (Parapenaeopsis stylifera) as a basic information for sustainable shrimp management.  A simple random sampling technique was used to sample the shrimp. The results showed that female shrimp dominated the catch of kiddy shrimp in Mukomuko waters. The growth pattern of kiddy shrimp showed a negative allometric pattern.  The gonadal maturity level (GML/TKG) of kiddy shrimp was dominated by TKG II and TKG III categories.  The value of fishing mortality (F) for the growth parameters of Kiddy shrimp was higher than natural mortality (M). The exploitation rate (E) of Kiddy shrimp was 0.78. The SPR value of kiddy shrimp was 0.21 or 21% moderate or close to overexploitation.  This study recommends three management options: replacing shrimp trawls with environmentally friendly fishing gear, opening and closing fishing areas and seasons, and reducing fishing effort.